Polygonum elazigense sp. nov. (Polygonaceae), a new species from Eastern Anatolia (Türkiye) - Behçet, Lütfi̇; Gülbasan, İbrahi̇m Hali̇l (Phytotaxa, 2025)
Polygonum elazigense (Polygonaceae) is described as a new species from eastern of Türkiye. It is similar to Polygonum luzuloides from which differs being much thicker, and by its lignified lower parts and multi-branched stem, as well as leaf and fruit structures and a height exceeding 1 m. In addition to the ecology of P. elazigense, IUCN conservation status, distribution map (including related species) are also given.